Advances in S–N bond formation via electrochemistry: a green route utilizing diverse sulfur and nitrogen sources. Issue 7 (8th March 2023) - Ye, Zenghui; Zhang, Xi; Ma, Weiyuan; Zhang, Fengzhi
Abstract : This review summarizes recent advances in S–N bond formation via electrochemistry from diverse sulfur and nitrogen sources to valuable sulfur–nitrogen-bond-containing compounds, such as sulfenamides, sulfinamides, sulfonamides, sulfoximines, isothiazoles and thiadiazoles. Abstract : Sulfur–nitrogen-bond-containing compounds, including SN bonds, have attracted a lot of attention from chemists because of their importance in organic synthesis, natural products, pharmaceuticals, pesticides, and materials. Thus, the development of green and sustainable synthetic methods to construct biological and synthetically important S–N bonds is having a great influence on the chemistry community. Electro-organic synthesis has emerged as a powerful green and sustainable tool for building chemical bonds over the last decade. This review summarizes recent advances in electrochemical S–N bond formation from diverse sulfur and nitrogen sources for synthesizing valuable sulfur–nitrogen-bond-containing compounds, such as sulfenamides, sulfonamides, sulfoximines, isothiazole, and thiadiazoles.